From long-term sickness absence to disability retirement: diagnostic and occupational class differences within the working-age Finnish population - Laura Salonen; Jenni Blomgren; Mikko Laaksonen (BMC, 2025)
Background: It is well documented that sickness absence is strongly associated with disability retirement. A long-term sickness absence (LTSA) in particular increases the risk of disability retirement, but little is known about the variation of this risk across diagnostic causes. Further, as occupational classes differ in their diagnostic profiles, it is likely that the role of diagnosis in the pathway from LTSA to disability retirement varies between occupational classes. We examined how LTSA of different diagnostic causes predicts all-cause disability retirement and disability retirement due to the same diagnostic group or due to some other diagnostic group than that which caused the LTSA spell in different occupational classes.
Methods: Cox proportional hazards models were used to analyse a 70% random sample of all employed Finns aged 25-62 Finns in 2006 (N=1,458,288). Disability retirement was followed from 2007 to 2014. The risk of disability retirement was compared between occupational classes with at least one LTSA spell due to musculoskeletal diseases, mental disorders, respiratory diseases, or circulatory diseases and those who had no LTSA spells due to these diagnostic groups during 2005.
Results: Those who had LTSA due to musculoskeletal diseases or mental disorders transferred more often to disability retirement due to same diagnostic group, whereas those who had LTSA due to respiratory or circulatory diseases transferred more often to disability retirement due to some other diagnostic group. The largest occupational class differences in all-cause disability retirement were found among those with LTSA due to mental disorders. For men, the hazard ratios (HR) varied from HR 5.70 (95% confidence interval (CI) 5.00-6.52) in upper non-manual employees to 2.70 (95% CI 2.50-2.92) in manual workers. For women, the corresponding HRs were 3.74 (95% CI 3.37-4.14) in upper non-manual employees and 2.32 (95% 2.17-2.50) in manual workers.
Conclusions: The association between LTSA and disability retirement varies between diagnostic groups, and the strength of this association further depends on the person's occupational class and gender.